2007
DOI: 10.1007/s10620-007-9856-7
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Risk Factors for HCV-mono-infection, HIV-mono-infection, and HCV/HIV-co-infection in a Community Setting

Abstract: The prevalence of HIV infection in HCV patients is much lower than the prevalence of HCV infection in HIV patients. Whereas the higher prevalence of HCV infection in HIV is clearly related to drug abuse, the reasons for the lower prevalence of HIV infection in HCV patients has not been reported. The prevalence of non-sexual and sexual risk factors associated with acquisition of hepatitis C and HIV were studied in HIV-mono-infected, HCV-mono-infected, and HCV/HIV-co-infected individuals. None of the 114 HCV-mon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
7
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 17 publications
1
7
0
Order By: Relevance
“…This is consistent with other studies that have found that male sex, black race, and Hispanic ethnicity are associated with higher risk of HIV co-infection with HBV and HCV [10, 12, 17]. The HIV transmission risk categories of individuals at highest risk for HIV co-infection with HBV or HCV in NYC were also consistent with the transmission routes of and reported risk factors for HBV and HCV [10, 11, 1316, 18]. The largest proportion of HIV/HBV-infected individuals were MSM, while the largest proportion of HIV/HCV-infected and HIV/HBV/HCV-infected individuals had a history of IDU.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This is consistent with other studies that have found that male sex, black race, and Hispanic ethnicity are associated with higher risk of HIV co-infection with HBV and HCV [10, 12, 17]. The HIV transmission risk categories of individuals at highest risk for HIV co-infection with HBV or HCV in NYC were also consistent with the transmission routes of and reported risk factors for HBV and HCV [10, 11, 1316, 18]. The largest proportion of HIV/HBV-infected individuals were MSM, while the largest proportion of HIV/HCV-infected and HIV/HBV/HCV-infected individuals had a history of IDU.…”
Section: Discussionsupporting
confidence: 91%
“…Multiple clinical cohort and cross-sectional studies have studied the prevalence of and risk factors for HBV and HCV co-infection in groups of people living with HIV/AIDS (PLWHA) throughout the world [7,[10][11][12][13][14]. Another important method for assessing the prevalence of HIV co-infection with HBV and/or HCV and the characteristics of co-infected patients is to match surveillance data for each infection collected by state or local health departments [15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, three of them were known to be co-infected with HIV. It has been reported that equipment used during, before, or after sexual activity [ 33 ], high-risk sexual behaviour in general [ 34 35 ], as well as the use of drugs [ 36 37 ], could be associated to a higher risk of HCV transmission, showing a potential role of multifactorial risk behaviour instead of transmission through one dominant route.…”
Section: Discussionmentioning
confidence: 99%
“…The rather limited evidence available points to the independent role of various behavioral and socio-demographic factors. Behavioral factors include: longer periods of injection drug use [ 5 , 28 – 33 ]; receptive sharing of injection equipment [ 5 , 32 36 ]; frequent injection [ 5 , 31 – 33 , 35 ]; present or past incarceration [ 29 , 35 , 37 , 38 ]; drug use during incarceration [ 39 ]; and high risk sexual behavior [ 30 ]. Socio-demographic factors include: residence in metropolitan areas where injection drug use takes place [ 5 ]; female gender [ 5 ]; older age [ 5 , 39 ]; ethnicity (in northern American studies, e.g., Hispanic in [ 29 ] and Canadian aboriginal in [ 5 ]); and lower education [ 28 ].…”
Section: Introductionmentioning
confidence: 99%